2023
DOI: 10.1186/s12866-023-02806-z
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, sensitive, and specific detection of SARS-CoV-2 in nasopharyngeal swab samples of suspected patients using a novel one-step loop-mediated isothermal amplification (one-step LAMP) technique

Abstract: Background In the absence of effective antiviral drugs or vaccines, early and accurate detection of SARS-CoV-2 infection is essential to the COVID-19 pandemic. This study developed and evaluated a novel rapid One-Step LAMP assay to directly detect the SARS-CoV-2 RNA from nasopharyngeal (NP) swab samples of patients with suspected SARS-CoV-2 infection living in deprived areas in comparison to One-Step Real-time PCR. Methods Two hundred fifty-four NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 52 publications
3
2
0
Order By: Relevance
“…According to the obtained results, it seems that the RT-LAMP method was able to detect SARS-CoV-2 carriers, one week before emerging the clinical symptoms, while the RT-qPCR method is not able to detect carriers. In this study, there was no significant relationship between age and SARS-CoV-2 infection that was consistent with the results of the studies by Khanizadeh et al [ 32 ], and Novosad et al [ 41 ]. While in contrary to this a significant relationship between age and SARS-CoV-2 infection was reported in the study of XU et al [ 42 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…According to the obtained results, it seems that the RT-LAMP method was able to detect SARS-CoV-2 carriers, one week before emerging the clinical symptoms, while the RT-qPCR method is not able to detect carriers. In this study, there was no significant relationship between age and SARS-CoV-2 infection that was consistent with the results of the studies by Khanizadeh et al [ 32 ], and Novosad et al [ 41 ]. While in contrary to this a significant relationship between age and SARS-CoV-2 infection was reported in the study of XU et al [ 42 ].…”
Section: Discussionsupporting
confidence: 93%
“…Based on Cohen’s kappa test, the agreement rate between LAMP and RT-qPCR tests in the nasopharyngeal sample was 94% (27.4% and 27.1% positivity rate respectively) and 93% in the saliva sample (26.8% and 25.1% positivity rate respectively) which, was statistically significant ( P < 0.001). The results were consistent with the results in the study by Khanizadeh et al [ 32 ] in terms of the agreement between the two techniques showing the accuracy and reliability of the results of the One-Step LAMP technique compared to the One-Step RT-qPCR method. Several studies have reported that the LAMP technique is a simple, fast, and sensitive isothermal amplification technique.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Several studies evaluated and proved the high sensitivity and specificity of LAMP technology. In Khanizadeh et al (2023), the specificity and sensitivity of the one-step LAMP technique were evaluated for the detection of the SARS-CoV-2 virus from nasopharyngeal swabs without extracting viral RNA. The study demonstrates that the assay can detect 1 × 10 1 copies of SARS-CoV-2 RNA strands, showing the high sensitivity of this technique.…”
Section: Sensitivity and Specificity Of Lamp Technologymentioning
confidence: 99%
“…Optimally, the target DNA region should range between 130 to 300 bp to be amplified by LAMP (Das et al, 2022). LAMP is capable of targeting different, unique regions of the target sequence using multiple primers during the same reaction (Khanizadeh et al, 2023). Furthermore, LAMP is compatible with multiplexing; for example, Zhu et al (2020) developed a multiplex RT-LAMP coupled with a nanoparticle-based lateral flow biosensor (LFB) to diagnose COVID-19, where two genes of SARS-Cov-2 virus the ORF1ab (opening reading frame 1a/b) and N (nucleoprotein) are amplified simultaneously in a single-tube reaction.…”
Section: Number Of Targets and Nucleic Acid Selectionmentioning
confidence: 99%